If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(18-6x)/2=(-2x+6)
We move all terms to the left:
(18-6x)/2-((-2x+6))=0
We add all the numbers together, and all the variables
(-6x+18)/2-((-2x+6))=0
We multiply all the terms by the denominator
(-6x+18)-(((-2x+6)))*2=0
We get rid of parentheses
-6x-(((-2x+6)))*2+18=0
We move all terms containing x to the left, all other terms to the right
-6x-(((-2x+6)))*2=-18
| -8u+2(u+6)=-12 | | 5=17-3v | | 10x+5x-7x=40 | | 20c+c=4c-7 | | -4n-8=4(3n=2) | | -8x/60+18.50+-1.5x/50-2=1 | | -3(7p+5)-2(1-20p)=3(1+6p) | | x+7.5=2.5x | | -8x/60+18.50=-1.5x/50-20-8x/60+18.50=-1.5x/50-20-8x/60+18.50=-1.5x/50-20-8x/60+18.50=-1.5x/50-20-8x/60+18.50=-1.5x/50-20-8x/60+18.50=-1.5x/50-20-8x/60+18.50=-1.5x/50-20-8x/60+18.50=-1.5x/50-20-8x/60+18.50=-1.5x/50-20 | | 7a=6-5a+12 | | 14-5xN=3xN | | 2.45x=78.25 | | 1x=10000000x-1 | | 5(r-8)+r=-39+7r | | 0.4x+10.8=x-1.32 | | 4(4-5n)=3n+39 | | 2s-6+3=-24 | | -10(2x-2)+7(3x-6)-8=4-9 | | 6(2y+6)=44(9+3y) | | 55x−33(x−55)=−33+55 | | 10+x/3=1 | | 0.3x+17.6=x-1.37 | | 7+x=1÷2(4x-2) | | -33+x(-3)=0 | | 2x-4-3x=6 | | 2x-4+5x=3 | | (8a-23)+(9-20)=90 | | -3n(1-2n)+2(n+4)=0 | | 2(4x+2)=4x-12x(x-1 | | 20/22.5=8/x | | -(n-5)-7n=-19-5n | | -4+3s=20 |